2016
DOI: 10.1111/iej.12677
|View full text |Cite
|
Sign up to set email alerts
|

Influence of apical enlargement and complementary canal preparation with the Self‐Adjusting File on endotoxin reduction in retreatment cases

Abstract: Apical enlargement protocols were effective in significantly reducing endotoxin levels. Complementary preparation with the SAF system failed to eliminate residual endotoxin contents beyond those obtained with the R40 instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…, Silva et al . ). In addition, a high success rate has been demonstrated during the retreatments of mandibular molars using preparation sizes of 35 to 40 with tapers of .04 to .06 (He et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Silva et al . ). In addition, a high success rate has been demonstrated during the retreatments of mandibular molars using preparation sizes of 35 to 40 with tapers of .04 to .06 (He et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Silva et al . ). Moreover, a recent prospective cohort study reported a high success rate (89%) for the retreatments of mandibular molars using contemporary techniques and preparation sizes of 35 to 40 with taper sizes of .04 to .06 (He et al .…”
Section: Discussionmentioning
confidence: 97%
“…In addition, in the same table, it is possible to notice that, in both evaluated regions, all the systems significantly decreased the amount of filling material after the retreatment procedures where instruments of size 25 were used and complemented with instruments of size 40 (P<0.05). These results corroborate with other studies that point out the need to use an additional large instrument to improve the removal of filling material in order to achieve a better cleaning of root canal systems (5,(16)(17).…”
Section: Discussionsupporting
confidence: 91%